2018
DOI: 10.3892/or.2018.6420
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of RRM2 inhibits cell proliferation, causes cell cycle arrest and promotes the apoptosis of human neuroblastoma cells and in human neuroblastoma RRM2 is suppressed following chemotherapy

Abstract: Ribonucleotide reductase regulatory subunit M2 (RRM2) is a rate‑limiting enzyme for DNA synthesis and repair. RRM2 has vital roles in controlling the progression of cancer. In the present study, we investigated the RRM2 level in neuroblastoma tissues, analyzed its relationship with clinicopathological characteristics of neuroblastoma patients, and explored the effect of RRM2 on the biological functions of neuroblastoma cells. RRM2 levels in 67 pairs of neuroblastoma and matched adjacent non‑cancerous tissues w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…GNRH_signaling_pathway DNA_replication Cell_cycle elevated Cyclin B1 levels served as a biomarker for the prognosis of prostate cancer patients who were being treated with chemotherapy (Gomez et al, 2007). Ribonucleotide reductase regulatory subunit M2 (RRM2) is an enzyme that limits the rate of DNA synthesis and repair (Li et al, 2018;Wu et al, 2018). Mostly, RRM2 was overexpressed in PCa patients with a high Gleason score and an advanced T stage.…”
Section: P53_signaling_pathwaymentioning
confidence: 99%
“…GNRH_signaling_pathway DNA_replication Cell_cycle elevated Cyclin B1 levels served as a biomarker for the prognosis of prostate cancer patients who were being treated with chemotherapy (Gomez et al, 2007). Ribonucleotide reductase regulatory subunit M2 (RRM2) is an enzyme that limits the rate of DNA synthesis and repair (Li et al, 2018;Wu et al, 2018). Mostly, RRM2 was overexpressed in PCa patients with a high Gleason score and an advanced T stage.…”
Section: P53_signaling_pathwaymentioning
confidence: 99%
“…Li et al illustrated that RRM2 was overexpressed in human glioblastoma cells, and promoted proliferation, migration, and invasion of human glioblastoma cells 34 . Suppression of RRM2 inhibits cell proliferation, causes cell cycle arrest, and promotes the apoptosis of human neuroblastoma cells 35 . In our story, the investigation of differential expression in LUAD found that RRM2 was highly expressed in tumor tissues, which was subsequently examined in multiple independent cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…International Publisher adrenocortical cancer [8], lung cancer [9], nasopharyngeal cancer [10], gastric cancer [11] and neuroblastoma [12], as well as being a predictor of poor prognosis [13][14][15][16][17]. Our previous study had indicated that RRM2 plays a critical role in the diagnosis and treatment of cervical cancer [18].…”
Section: Ivyspringmentioning
confidence: 99%